Examination and counseling of gynecological cases during Corona Virus Disease 2019 (COVID-19) pandemic - I Gde Sastra Winata; Clara Amanda (Majalah Obstetri dan Ginekologi, 2021)
HIGHLIGHTS1. Clinical gynecology examinations must adapt to pandemic situation.2. It must pay attention to universal precautions, aseptic and sterile technique to minimize infection transmission.3. In terms of reducing contact, the need for examination are divided by priority into "now", "soon", or "later".4. Gynecology examinations can be carried out with direct examinations by medical personnel wearing proper personal protective equipment if needed.5. Patient counseling can be done by remote consultation or telemedicine. ABSTRACTCOVID-19 is a recent pandemic caused by the SARS COV-2 agent with a high incidence and mortality. The disease is transmitted through respiratory droplets and direct contact. Clinically this COVID-19 patient is mainly related to the respiratory tract symptoms. The current clinical classifications are divided into suspected, probable, and confirmed cases. To reduce transmission must pay attention to universal and hierarchical precaution, aseptic standards, and sterile techniques. The types of gynecological examinations during a pandemic are the same as those in general, except that the methods, settings, and priorities are different. The examination begins with screening to assess the risk of transmission so that it can determine the place of examination. The urgency of the examination, history of TOCC, local transmission, provider, and room conditions also need to be considered. Counseling during a pandemic can be done in person or by telemedicine. Counseling is provided for general and case-specific gynecological information. Each gynecological case requires a different focus on counseling.